2018
DOI: 10.1042/cs20171588
|View full text |Cite|
|
Sign up to set email alerts
|

Prader–Willi region non-protein coding RNA 1 suppressed gastric cancer growth as a competing endogenous RNA of miR-425-5p

Abstract: Gastric cancer (GC) is one of the major global health problems, especially in Asia. Nowadays, long non-coding RNA (lncRNA) has gained significant attention in the current research climate such as carcinogenesis. This research desires to explore the mechanism of Prader-Willi region non-protein coding RNA 1 (PWRN1) on regulating GC process. Differentially expressed lncRNAs in GC tissues were screened out through microarray analysis. The RNA and protein expression level were detected by quantitative real-time PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 39 publications
2
21
0
Order By: Relevance
“…Recently, it was reported PWRN1 acted as an active factor in suppressing human gastric cancer cell growth. 19 However, to the best of our knowledge, discovery in the present study is the first one to report the functional mechanism of PWRN1 in human GBM.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Recently, it was reported PWRN1 acted as an active factor in suppressing human gastric cancer cell growth. 19 However, to the best of our knowledge, discovery in the present study is the first one to report the functional mechanism of PWRN1 in human GBM.…”
Section: Discussionmentioning
confidence: 68%
“…In recent decades, strong evidence has demonstrated that lncRNAs may by aberrantly deregulated in human GBM tumors and closely associated with cancer patients' prognosis, thus making them potential candidates for diagnostic biomarkers or therapeutic targets for GBM. 13,14 In the present study, we suspected lncRNA of PWRN1, which has been shown to be dysregulated in several types of human cancers, [19][20][21]25 is also aberrantly expressed in human GBM, and functionally involved in GBM cell regulation. Based on this hypothesis, we used a systemic approach to assess the expression profile and possible regulatory mechanisms of PWRN1in GBM.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Recently, it was reported that DLEU2 was involved in several types of cancer and DLEU2 exon 9 was an independent marker of poor prognosis in patients with esophageal adenocarcinoma (31). Aberrant expression levels of TCL6 were involved in clear cell renal carcinoma by regulating the PI3K/AKT pathway and PWRN1 inhibits gastric cancer cell proliferation and metastasis via p53 signaling pathway (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…Wawrzik et al (107) hypothesized that the action of PWRN1 on the imprinting mechanism may be indirect through keeping the paternal allele in an open chromatin configuration, allowing access to transcription factors (107). The main limitation for further confirmation studies is the lack of gene orthology in mice (108)(109)(110).…”
Section: Genotype-phenotype Relationships In Prader-willi Syndromementioning
confidence: 99%